1981
DOI: 10.1128/aem.41.3.585-592.1981
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and R-plasmids in food chain Salmonella: evidence of plasmid relatedness

Abstract: Objective: A major preventable contributor to healthcare costs among older individuals is fall-related injury. We sought to validate a tool to stratify such risk based on readily available clinical data, including projected medication adverse effects, using statewide medical claims data. Design: Sociodemographic and clinical features were drawn from health claims paid in the state of Massachusetts for individuals aged 35-65 with a hospital admission for a period spanning January-December 2012. Previously devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1983
1983
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…in animals. Our study, however, showed higher resistance than that obtained in other studies (Bell et al 1980;Bezanson & Lior 1980;Bezanson et al 1981;Falbo et al 1982;Alcaide & Garay 1984). Of the total salmonellas tested 26.7% exhibited resistance to two or more antibiotics.…”
Section: Discussioncontrasting
confidence: 72%
“…in animals. Our study, however, showed higher resistance than that obtained in other studies (Bell et al 1980;Bezanson & Lior 1980;Bezanson et al 1981;Falbo et al 1982;Alcaide & Garay 1984). Of the total salmonellas tested 26.7% exhibited resistance to two or more antibiotics.…”
Section: Discussioncontrasting
confidence: 72%
“…Biotype 4 has been commonly observed in various S. typhimurium phage types (R. Khakhria, unpublished results). In addition, the majority of Salmonella strains isolated in Canada are sensitive to antibiotics (3,7). Thus, it could not be ascertained at this level whether the continued recovery of antibiotic-sensitive S. typhimurium phage type 10, biotype 4 isolates constituted detection of the true etiologic agent.…”
Section: Resultsmentioning
confidence: 99%
“…The linkage between drug resistance in animal bacteria and clinical strains has long been suggested (Anderson et al 1975;Bezanson et al 1981;Mee & Nikoletti, 1983). Indeed contamination of carcasses by animal faecal flora is a common occurrence at slaughter (Linton et al 1976).…”
Section: Discussionmentioning
confidence: 99%